Harmony in Academic Climate: Implementation of Religious Moderation Policy in Indonesia Islamic Higher Education Institutions (PTKIN) - Muhibbuthabry Muhibbuthabry; Rahmad Syah Putra; Abd. Razak; Amrullah Amrullah; Amirul Haq RD; Diva Dina (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
Religious moderation has become a strategic policy agenda in Indonesia's Islamic higher education system, yet its implementation across State Islamic Higher Education Institutions (PTKIN) remains uneven. This study aims to examine how the Religious Moderation Policy (RMP) is translated into institutional governance, curriculum practices, lecturer capacity, student engagement, and the sustainability of Centers for Religious Moderation (Rumah/Pusat Moderasi Beragama). Using a convergent mixed-methods design, the study collected quantitative survey data from lecturers and students and qualitative data through semi-structured interviews, focus group discussions, and institutional document analysis across ten PTKIN representing different Indonesian regions. The findings show that RMP implementation reached an overall index of 79.6%, categorized as good and approaching very good, with student engagement scoring highest (84%) and institutional sustainability scoring lowest (76%). Qualitative evidence indicates that successful implementation depends not only on formal regulations but also on leadership commitment, lecturer preparedness, participatory campus culture, and stable budgetary support. In several institutions, moderation has begun to function as an academic ethos embedded in learning, student activities, and community outreach; in others, it remains limited to symbolic programs and administrative compliance. The study implies that religious moderation in PTKIN should be strengthened through measurable policy indicators, sustainable institutional funding, lecturer development, and participatory governance so that moderation becomes a lived academic climate rather than a temporary policy campaign.